Herbarium specimen image of Rorippa islandica (Oeder) Borbás, part of the collection of Natural History Museum, University of Tartu - Natural History Museum, University of Tartu (Zenodo, 2018)
Part of a training dataset of scanned herbarium specimens. The data paper and a summary landing page will be published on Zenodo as it gets published. Content of this deposition: - A JSON-LD datafile listing the label data associated with this herbarium specimen. The Darwin and Dublin Core data standards are used for most values. - A JPEG image file of the scanned herbarium sheet. - A lossless TIFF image from which the JPEG image has been derived.